2012
DOI: 10.1254/jphs.11186fp
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside Stimulates Cell Proliferation and Prevents Cell Apoptosis in Intestinal Epithelial MODE-K Cells by Up-Regulation of Transforming Growth Factor-β1 Expression

Abstract: Abstract. Cistanche deserticola MA (C. deserticola) has been widely used as a laxative herbal in herbal medicine for the treatment of irritable bowel syndrome or constipation, and echinacoside (ECH) is one of the major bioactive ingredients in this herbal. Our aim was to investigate the effect of ECH on intestinal epithelial cell growth and death. MODE-K, an intestinal epithelial cell line, was used as an in vitro model of the intestine. Cell proliferation was measured by methylthiazol tetrazolium (MTT) assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Furthermore, a new and a known corresponding sugar ester, kankanose 22) (56) and cistanoside F 89) (57), were also obtained (Chart 3). (69). Among the isolates, D-mannitol (69) gave the most highest isolation yield in our study.…”
Section: Chemical Constituentsmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, a new and a known corresponding sugar ester, kankanose 22) (56) and cistanoside F 89) (57), were also obtained (Chart 3). (69). Among the isolates, D-mannitol (69) gave the most highest isolation yield in our study.…”
Section: Chemical Constituentsmentioning
confidence: 55%
“…[59][60][61] Among them, echinacoside 62,63) (28) and acteoside [64][65][66][67] (29, also called verbascoside, kusaginin, and orobanchin) are representatives of the well-studied phenylethanoid glycosides and have been reported to possess a number of important bioactive properties such as antioxidative, neuroprotective, nitric oxide radical scavenging, antihepatotoxic, and antiosteoporotic activities. [2][3][4]6,[59][60][61][68][69][70][71][72][73][74][75][76][77] As phenylethanoid glycoside constituents from the stems of C. tubulosa, we have isolated the above-mentioned echinacoside 78) (28) and acteoside 78) (29) (54), and campneoside II 86,87) (55). Furthermore, a new and a known corresponding sugar ester, kankanose 22) (56) and cistanoside F 89) (57), were also obtained (Chart 3).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…After 24 hr, the medium was changed and PPD was added at different concentrations. After treatment for 48 hr, all adherent cells were collected with 0.05% trypsin, including the floating cells in the medium, and centrifuged for 5 min at 600 g. Then, the cells were double stained with Annexin-V-(FITC) and propidium iodide (PI) (Becton Dickinson, San Diego, CA) according to the manufacturer's instructions (15). Untreated cells were used as control.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been reported that ECH exhibits a protective role by inhibiting apoptosis and inflammatory signals in somatic cells, such as neuronal and intestinal epithelial cells (16)(17)(18)(19), it remains elusive whether ECH controls cancerous cell growth and proliferation. To test this, a cell survival assay was conducted by treating SW1990 cells, derived from a grade II pancreatic adenocarcinoma, with titrated doses of ECH as shown in Fig.…”
Section: Ech Suppresses Tumor Cell Growthmentioning
confidence: 99%
“…Also, ECH has been shown to have protective effects on nerve tissue and improve behavioral disorders in murine models of Parkinson's disease (18). Notably, it has been found that ECH promotes cell proliferation and inhibits apoptosis in the mouse intestinal epithelial MODE-K cells (19). Thus far, however, less attention has been paid to the potential role of ECH in cancer prevention.…”
Section: Introductionmentioning
confidence: 99%